Assessing Renal Function for Kidney Donation. How Low Is Too Low? - Laham, Gustavo; Ponti, Juan Pablo; Soler Pujol, Gervasio (Frontiers in Medicine, 2022)
Kidney transplantation (KT) is the treatment of choice for patients with end-stage kidney disease (ESKD) with decreased morbi-mortality, improved life quality, and reduced cost. However, the shortage of organs from deceased donors led to an increase in KT from living donors. Some stipulate that living donors have a higher risk of ESKD after donation compared to healthy nondonors. The reason for this is not clear. It is possible that ESKD is due to the nephrectomy-related reduction in GFR, followed by an age-related decline that may be more rapid in related donors. it is essential to assess donors properly to avoid rejecting suitable ones and not accepting those with a higher risk of ESKD. Glomerular filtration rate (GFR) is a central aspect of the evaluation of potential donors since there is an association between low GFR and ESKD.The methods for assessing GFR are in continuous debate, and the kidney function thresholds for accepting a donor may vary according to the guidelines. While direct measurements of glomerular filtration rate (mGFR) provide the most accurate evaluation of kidney function, guidelines do not systematically use this measurement as a reference. Also some studies have shown that the GFR decreases with age and may vary with gender and race, therefore the lower limit of GFR in patients eligible to donate may vary based on these demographic factors. Finally, it is known that CrCl overestimates mGFR while eGFR underestimates it, therefore another way to have a reliable GFR could be the combination of 2 measurement methods.